2017
DOI: 10.15252/msb.20167058
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism for microbial population collapse in a fluctuating resource environment

Abstract: Managing trade‐offs through gene regulation is believed to confer resilience to a microbial community in a fluctuating resource environment. To investigate this hypothesis, we imposed a fluctuating environment that required the sulfate‐reducer Desulfovibrio vulgaris to undergo repeated ecologically relevant shifts between retaining metabolic independence (active capacity for sulfate respiration) and becoming metabolically specialized to a mutualistic association with the hydrogen‐consuming Methanococcus maripa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
35
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(37 citation statements)
references
References 63 publications
0
35
0
Order By: Relevance
“…In light of these observations, in a previous study we investigated whether conditional regulation contributes to robustness of a model microbial population growing under variable conditions in contrast to the stable conditions noted above. One of the DvH regulatory genes that accumulated mutations during evolution in syntrophy (DVU0744 – a sigma‐54 family transcription factor), was identified as a potential novel transcriptional regulator of SR using a network model of gene expression under a range of conditions and a DVU0744 transposon insertion mutant was generated (Turkarslan et al ., ). The growth rate of the DVU0744::Tn5 mutant was reduced relative to wild type under conditions of excess sulfate.…”
Section: Introductionmentioning
confidence: 97%
See 3 more Smart Citations
“…In light of these observations, in a previous study we investigated whether conditional regulation contributes to robustness of a model microbial population growing under variable conditions in contrast to the stable conditions noted above. One of the DvH regulatory genes that accumulated mutations during evolution in syntrophy (DVU0744 – a sigma‐54 family transcription factor), was identified as a potential novel transcriptional regulator of SR using a network model of gene expression under a range of conditions and a DVU0744 transposon insertion mutant was generated (Turkarslan et al ., ). The growth rate of the DVU0744::Tn5 mutant was reduced relative to wild type under conditions of excess sulfate.…”
Section: Introductionmentioning
confidence: 97%
“…We found that all replicates of the wild type DvH co‐culture were unable to persist with repeated transfer between these growth states, some collapsing after as few as 3 SR/ST transitions. Remarkably, all replicates of a co‐culture with DvH DVU0744::Tn5 persisted across the same transitions without collapse (Turkarslan et al ., ). A series of additional measurements were used to explore the mechanism underlying this collapse in wild type and persistence in the mutant.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…In the first 300 generations of evolution of the syntrophy I study, changes in both Desulfovibrio vulgaris and Methanococcus maripaludis contributed to substantial increases in the number of cells produced from a fixed amount of a single limiting resource and resulted in substantial increases in growth of the community . By 1000 generations, the communities grew about three times faster than the ancestor, a change that was correlated in D. vulgaris with loss of its ability to respire sulfate, a trait that has a substantial impact on survival outside syntrophy and may impede performance in syntrophy …”
Section: Adaptation To Mutualismmentioning
confidence: 96%